Mediating Role of Organizational Citizenship Behavior in Workplace Dynamics: A Literature Review on Workload, Work Culture, Motivation, Job Stress, Social Support, and Employee Performance - Utami, Batina Yulia; Elmanisar, Velnika; Hadiyanto, Hadiyanto; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
The purpose of this literature review is to analyze how OCB serves as a critical mediator between key workplace factors such as workload, work culture, motivation, job stress, social support, and employee performance. By systematically analyzing relevant texts, books, and peer-reviewed journals, this library-based study synthesizes extant theoretical frameworks and empirical findings to highlight the critical role of OCB. The results reveal that job satisfaction, competence, and leadership are key determinants shaping employees’ willingness to exhibit extra-role behaviors that benefit the organization as a whole. In turn, employees who perceive fairness, autonomy, and opportunities for skill development are more likely to take on additional responsibilities and demonstrate a strong commitment to organizational success. The discussion underscores that strategic interventions aimed at enhancing job satisfaction, building competencies through continuous learning, and cultivating effective leadership styles can enhance OCB, thereby mediating the influences of workload, culture, motivation, stress, and social support on performance outcomes. The review concludes that OCB acts as a vital catalyst for boosting overall organizational performance by bridging critical gaps between individual attitudes and broader institutional goals. Ultimately, OCB fosters a collaborative climate that promotes agility and innovation.